Alcohol Consumption and Subclinical Findings on Cognitive Function, Biochemical Indexes, and Cortical Anatomy in Cognitively Normal Aging Han Chinese Population - Sun, Lin; Xu, Hua; Zhang, Jie; Li, Wei; Nie, Jing; Qiu, Qi; Liu, Yuanyuan; Fang, Yuan; Yang, Zhi; Li, Xia; Xiao, Shifu (Frontiers in Aging Neuroscience, 2018)
Background: Binge drinking of alcohol is associated with brain damage, but less is known about relationship of light-to-moderate alcohol consumption with cognitive function, biochemical indexes, and cortical anatomy. Previous findings indicate debate on whether light-to-moderate drinking has any health benefits. We investigated cortical thickness and its association with alcohol consumption and cognitive functions in a non-dementia aging Han Chinese population. Methods: 940 non-dementia aging subjects were included in our study (alcohol n=149; non-alcohol n=791). Among them, 572 received blood biochemical tests including liver function and lipid metabolism (alcohol n=100; non-alcohol n=472) and 141 had brain magnetic resonance imaging (alcohol n=27; non-alcohol n=114). The Beijing version of the Montreal Cognitive Assessment (MoCA) and the Chinese version of the neuropsychological test battery (NTB) were used to assess cognitive functions. Results: There was no significant difference in cognitive functions between alcohol and non-alcohol groups in the overall database. Similarly, there was no significant difference in liver function and lipid metabolism between two groups in the sub-database. The left superiortemporal gyrus was one of age sensitive regions and alcohol consumption was significantly associated with thinner cortex of the left superiotemporal cluster in the sub-database. Conclusion: Alcohol consumption was not significantly associated with better or worse cognitive function and biochemical indexes abnormality, however, significantly associated with thinner cortex of the left superiortemporal gyrus in cognitively normal aging Han Chinese population.